Decoating of TiN-Coated Cemented Tungsten Carbide Tools by Laser Ablation for Remanufacturing Purposes - Oliver Maurer; Roger Escolano Benach; Dirk Bähre (Circular Economy and Sustainability, 2026)
Cutting technologies are in wide industrial use and rely on durable tools to machine as many parts as possible before the tool is worn out. Cemented carbide tools such as indexable inserts provide several cutting edges and are readily replaceable by new ones. They consist of a cemented carbide body with hard coatings of oxide or non-oxide ceramics. The cemented carbide body consumes large amounts of energy in several sintering stages at its begin of life. In order to save energy and resources that would be required to manufacture new inserts, it would promote sustainability to remanufacture and recondition used inserts and, by that, maintain the cemented carbide body. Therefore, this study aims to remove hard non-oxide ceramic coatings from the cemented carbide with a commercially available laser engraving system. Laser ablation offers less geometrical constraints than machining approaches and does not depend on the hardness of the coating. As a result, this study offers suitable laser ablation parameters to remove TiN coatings from commercially available inserts and proves that this process consumes less energy than producing new inserts. This gives the opportunity to selectively decoat and recondition indexable inserts in the future. Thereby, the energy-intensive production of new cemented carbide bodies is avoided allowing the cutting technology to reach higher sustainability goals.
Keywords: 330; Cemented carbide tools; Laser ablation; Remanufacturing; Decoating